ACUTE SEROUS RETINAL DETACHMENT IN IDIOPATHIC PULMONARY ARTERIAL HYPERTENSION. Issue Volume 11:Issues 3(2017:Summer) (2017) - Martiano, David; Chevreaud, Olivier; Lam, Delphine; Cohen, Salomon Y.; Souied, Eric H.
Abstract : Purpose: To report the case of a 44-year-old woman with acute transient visual loss likely because of idiopathic pulmonary arterial hypertension. Methods: Case report imaged with fundus photographs, spectral-domain optical coherence tomography, fundus autofluorescence, and fluorescein and indocyanine green angiographies. Results: The patient complained of unilateral vision loss with metamorphopsia. Fundus examination of the right eye showed serous macular detachment and retinal folds. Fluorescein angiography and indocyanine green angiography showed delayed choroidal filling with multiple choroidal perfusion defects and dye leakage from areas of multiple pigment epithelial detachments. Spectral-domain optical coherence tomography showed a thick choroid. Medical history included idiopathic pulmonary arterial hypertension treated with tadalafil. Ocular signs regressed spontaneously within 1 week. Conclusion: Transient severe choroidal filling defects with subretinal exudation may be observed in idiopathic pulmonary arterial hypertension. The present case raised the questions of the triggering factor of the acute decompensation of the blood–retinal barrier and the cause of its spontaneous regression. Abstract : A 44-year-old woman treated with tadalafil for idiopathic pulmonary arterial hypertension presented with transient visual loss and ocular manifestations of acute choroidal ischemia including serous retinal detachment and yellow spots of the fundus.